2018
DOI: 10.1021/acs.energyfuels.7b03645
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Capture by Kaolin, Part 1: KOH

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(102 citation statements)
references
References 74 publications
(170 reference statements)
6
95
1
Order By: Relevance
“…[28]. In the raw kaolinite, Si atoms were assigned to a Q 3 Table 3, more than 80% of kaolinite-characterized Si was converted for flash calcination. The formation of mullite-characterized Si appeared at 1200 • C, in agreement with the result of XRD.…”
Section: Coordination Change Of Si and Almentioning
confidence: 99%
See 2 more Smart Citations
“…[28]. In the raw kaolinite, Si atoms were assigned to a Q 3 Table 3, more than 80% of kaolinite-characterized Si was converted for flash calcination. The formation of mullite-characterized Si appeared at 1200 • C, in agreement with the result of XRD.…”
Section: Coordination Change Of Si and Almentioning
confidence: 99%
“…Coal, biomass and solid waste contain Na, K, Pb, Cd and other alkali/heavy metals. During combustion, gasification and other processes, these semi-volatile metals are prone to cause the problems such as boiler slagging, ash deposition of heat transfer area, high-temperature corrosion, and emissions of heavy metals and ultra-fine particles [1][2][3][4][5]. Kaolinite can adsorb alkali/heavy metal vapor at high temperatures, and then be captured by dust removal equipment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have indicated that the main source of element K in heating surface deposits is gas phase K in biomass combustion [4,5,[8][9][10]. In this study, with the condition of combustion temperature (800 °C) and low Cl content in fuel, K probably enters the gas phase mainly in the form of KOH in place of KCl and K2SO4.…”
Section: Migration and Deposition Of Alkali Metalmentioning
confidence: 77%
“…The dominant elements in biomass ash are Ca, K, Cl and S [2,3]. During combustion, K element in biomass fuel is released to the gas phase in the form of KCl, KOH and K 2 SO 4 [4][5][6][7][8][9][10]. These potassium-containing compounds cause severe slagging due to their low melting temperature [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%